Strategy in the global mobile phone industry - Raza, F.A. Hashim (KDI School, 2000)
The global mobile phone industry has emerged as an extremely competitive yet attractive industry, characterized by a blend of high technology, intense competition and attractive markets. Particularly in the last decade, it has gone through remarkable advancements simultaneously in technology, competitiveness and customer orientation, leaving its strategy makers completely mesmerized. This dynamic transformation is an outcome of a multi dimensional journey performed by the industry in the last twenty years. On the technology dimension, the journey from 1st to 3rd generation phones and from a variety of un compatible technical standards to a single universal wireless standard, on the competitiveness dimension, the journey from close to monopolistic competition to a cutting-edge competitive environment with a vast array of players and on the customer dimension, the industry leaped from hundreds of them to 900 million in 2001. During the course of this transformation, companies like Nokia ascended the growth ladder to #1 in the wireless world from nowhere, whereas a number of other companies even lost their existence in the process. These extremes amongst the industry players are peculiar of any competitive industry, but in case of wireless industry this environment has emerged in less than 20 years, which is so far unprecedented. Lately, with the advent of the 3rd generation phones, the industry entered into an entirely new dimension, convergence with other industries like computers, software, Internet solutions etc. This convergence has posed serious implications for the industry managers. The global mobile phone industry, at the moment, presents an ideal case study for the strategy makers in a truly global and competitive industry. An endeavor has, therefore, been made, in this thesis; to identify the challenges faced by the industry, to define the present opportunities and to analyze the strategies of the major players of the industry, followed by a summary of the key findings from the global mobile phone industry
Thesis(Master) --KDI School:Master of Business Administration,2000